Applied Mathematics and Computational Physics (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As faster and more efficient numerical algorithms become available, the understanding of the physics and the mathematical foundation behind these new methods will play an increasingly important role. This Special Issue provides a platform for researchers from both academia and industry to present their novel computational methods that have engineering and physics applications.